An analysis of students' literacy ability in mathematics teaching with realistic mathematics education based on lesson study for learning community - Rohman, Syaifur; Susanto; Hobri; Saiful; Sahnawi (Journal of physics. Conference series, 2019)
The aims of this research is to explore students' literation abilities descriptively and teacher's response in Math instruction of lesson study for learning community based realistic mathematics education. Literation ability is the ability of the individual to form, use, and interpret mathematics in various contexts. Realistic mathematics education aims to present the real world context to students. The research subjects were 29 seventh grade students of MTs Ma'arif Ambulu. The descriptive approach of qualitative method becomes a choice to understand literation ability and teachers' response. Data collection was done by observation, PISA test questions, student and teacher interviews, and documentation. Data analysis was using the theory of induction and reduction. The results of the research showed that the students were positively responding to this approach. The ratios of mathematical literacy ability based on the total students respectively were 44.83% on level 4 and 31.03% on level 5, and 24.14% on level 3. The teacher's response showed that this approach could change the atmosphere to be more active between the teacher and the students as well as the students with their fellow. The teacher could optimize his role; recognize his weakness through reflection with the team so that he had the opportunity to prepare the next strategy to improve quality.